Molecularly imprinted polymer synthesis using RAFT polymerisation - Cormack, Peter A.G.; Faizatul Shimal Mehamod (Universiti Kebangsaan Malaysia, 2013)
In this paper, the synthesis and characterisation of caffeine-imprinted polymers are described. The polymers were prepared in monolithic form via both reversible addition-fragmentation chain-transfer (RAFT) polymerisation and conventional free radical polymerisation, using methacrylic acid and ethylene glycol dimethacrylate as the functional monomer and crosslinking agent, respectively. The potential benefits in applying RAFT polymerisation techniques towards the synthesis of molecularly imprinted polymers (MIPs) are explored and elucidated. The pore structures of the polymers produced were characterised by nitrogen sorption porosimetry and the molecular recognition properties of representative products were evaluated in high-performance liquid chromatography (HPLC) mode. Molecular imprinting effects were confirmed by analysing the relative retentions of analytes on imprinted and non-imprinted HPLC stationary phases. It was found that a caffeine-imprinted polymer synthesised by RAFT polymerisation was superior to a polymer prepared using a conventional synthetic approach; the imprinting factor and column efficiency were found to be higher for the former material.